Uma proposta de trabalho com o gênero discursivo anúncio publicitário na formação crítica do leitor - Cruz, Silvana Aparecida Costa da (2017)
In this study we present a work proposal that, articulated to Professional Master in Letters (PROFLETRAS) - UNIOESTE - Cascavel, class 2016/2018, is based on the theme the commercial advertising genre in the critical formation of the reader. In the perspective of seeking the development of critical awareness of the act of reading, we focus, through the work with the selected genre, the critical formation of readers of the 9th grade of Elementary School. Thus, we proposed to find possible answers to the following question: How to enable 9th graders to exercise / develop their critical ability through a reading job with the discursive advertising genre? So, the general objective that guided this research was to create a didactic reading proposal with the discursive advertising genre to enable 9th graders to exercise / develop their critical capacity. For this, we support our studies in the reading conceptions of some researchers as Bakhtin (2003 [1992]), Luckesi et al. (1998), Freire (1992, 2005), Carvalho (2006), Hila (2009), Koch and Elias (2010), Menegassi (2010a, 2010b), Costa-Hübes and Barreiros (2014) , among others, searching methodologies and alternatives for teaching critical reading through work on discourse genres in the school environment, in the final grades of elementary school. In this sense, we developed a research supported by Applied Linguistics, being the same qualitative interpretative type and based on the method of action research. As a result, we obtained a significant improvement in the reading abilities of the students involved in the research, which proves the relevance of the work on reading in a critical and discursive perspective, based on the sociological and dialogical method of language.